Oral lesions of viral, bacterial, and fungal diseases in children: A decision tree - Guillouet, Charlotte; Riou, Margot C.; Duong, Lucas T.; de La Dure-Molla, Muriel; Fournier, Benjamin P. J. (Frontiers in Pediatrics, 2022)
Oral mucosal lesions are common in the pediatric population and, apart from traumatic and tumoral etiologies, they can be symptoms of viral, bacterial, fungal or parasitic diseases. Yet, pediatricians and pediatric dentists find it challenging to reach a diagnosis and provide appropriate care when facing lesions of the masticatory or lining mucosa, of the hard or soft palate, of the tongue or salivary glands. Here, we propose a decision tree for the diagnosis of the most frequent viral, bacterial, fungal and parasitic diseases starting from their oral lesions in children. By first focusing on describing the elementary lesion itself before its localization and characteristics, it aims to guide the practitioner towards the diagnosis and any necessary complementary exams. To generate this tool, we conducted a literature review of the childhood viral, bacterial, fungal and parasitic diseases with oral mucosal symptoms. For each of the 42 reported diagnoses - 20 viral, 9 bacterial, 5 fungal and 8 parasitic - we collected the infection mechanism and agent(s), the oral lesions and their description, the associated systemic signs and the incidence/prevalence. In fine, our decision tree indexes the 28 diseases for which epidemiological data was available, mainly in Europe and the United States.